Effect of high-fat-fructose diet on synaptic plasticity in hippocampus and lipid profile of blood serum of rat: pharmacological possibilities of affecting risk factors - Micháliková D.; Kaprinay B. Tyukos; Lipták B.; Švík K.; Slovák L.; Sotníková R.; Bezek Š.; Gáspárová Z. (Sciendo, 2018)
The aim of this study was to determine pharmacological possibilities of influencing the risk factors of metabolic syndrome (MetS). Hypertriacylglycerolemic (HTG) rats fed with high-fat-fructose diet (HFFD) were used as a model of the MetS. Wistar rats fed with standard diet were used as negative control group. HTG rats fed with HFFD for 8 weeks were used as positive control group. The effects of atorvastatin and SMe1EC2 were tested. The compounds were administered to the HTG rats after 5 weeks of HFFD, once a day for 3 weeks. After 8 weeks, the blood serum lipid profile and electrophysiology of neurotransmission in hippocampal sections were evaluated in vitro. SMe1EC2 and atorvastatin had a significant effect on total cholesterol (TC) and low-density lipoprotein cholesterol (LDL-cholesterol) and atorvastatin had a significant effect on triacylglycerols (TGs). SMe1EC2 improved the long-term potentiation (LTP) course in the hippocampus.